2014
DOI: 10.1111/1574-6941.12384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long-term N, P, K, and NPK fertilization on the composition and potential functions of the bacterial community in grassland soil

Abstract: Soil abiotic and biotic interactions govern important ecosystem processes. However, the mechanisms behind these interactions are complex, and the links between specific environmental factors, microbial community structures, and functions are not well understood. Here, we applied DNA shotgun metagenomic techniques to investigate the effect of inorganic fertilizers N, P, K, and NPK on the bacterial community composition and potential functions in grassland soils in a 54-year experiment. Differences in total and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(117 citation statements)
references
References 45 publications
(55 reference statements)
6
109
2
Order By: Relevance
“…In this study, we may assure that the preparation of soil for soybean crop was the main cause of the difference in pH between soils. However, not only pH correlated with the structure of microbial communities in these soils, showing that other soil parameters are important in shaping the communities, as shown by others (Faoro et al, 2010;Jesus et al, 2009;Kuramae et al, 2012;Lauber et al, 2008;Mendes et al, 2014;Navarrete et al, 2013;Pan et al, 2014). Our results show that Al saturation index and Al were the factors that presented correlation with more number of bacterial phyla.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, we may assure that the preparation of soil for soybean crop was the main cause of the difference in pH between soils. However, not only pH correlated with the structure of microbial communities in these soils, showing that other soil parameters are important in shaping the communities, as shown by others (Faoro et al, 2010;Jesus et al, 2009;Kuramae et al, 2012;Lauber et al, 2008;Mendes et al, 2014;Navarrete et al, 2013;Pan et al, 2014). Our results show that Al saturation index and Al were the factors that presented correlation with more number of bacterial phyla.…”
Section: Discussionsupporting
confidence: 81%
“…Also, the long-term effect of land-use change on microbial communities is of paramount importance and is ultimately required for evaluating sustainability of different management systems (Rasmussen et al, 1998). Yet few studies have been conducted in agroecosystem in an extended period of time (Hartmann et al, 2015;Pan et al, 2014) and this information will stimulate the development of better soil management strategies focused on minimizing the environmental perturbation in order to promote sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The potential causes of this correlation are the following: (1) integration of pH with other soil physical, chemical, and microbiological properties and (2) a slight variation in the soil pH that could expose microbes to stress, or in other words, the sensitivity of the microbial cell to environmental change (Fierer and Jackson, 2006). Some studies indicated that several parameters other than pH and elements (e.g., Mg, Al, and Cd) are also correlated with specific bacterial groups and structural alternation of microbial communities (Pan et al, 2014;Jesus et al, 2009;Mendes et al, 2015). The vegetation cover might affect the diversity and structure of the soil microbial community because the differences in plant community compositions can contribute to changes in litter quality and quantity, which then alter the content and cycling processes of soil nutrients (Miki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that soil microbial communities can shift in response to nutrient additions at individual grassland sites (18,20,22,24), relating these taxonomic or phylogenetic shifts to changes in the functional attributes of these communities is not trivial. Simply documenting how communities shift in composition might not tell us how the aggregated traits of these communities change in response to nutrient additions because soil microorganisms are incredibly diverse, and most soil microbial taxa remain uncharacterized (25).…”
Section: Significancementioning
confidence: 99%